2016
DOI: 10.2147/ndt.s94648
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report of improved sleep quality in patients with dry eye disease after initiation of topical therapy

Abstract: PurposeDry eye disease (DED) is potentially associated with sleep and mood disorders. This study evaluated sleep quality in patients with DED using a questionnaire-based survey before and after topical eyedrop treatment. The effectiveness of sleep and ophthalmic services in assisting with sleep problems in patients with eye disease was also assessed.MethodsSeventy-one consecutive patients with DED visiting eight general eye clinics in various locations answered a questionnaire containing the Pittsburgh Sleep Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
(32 reference statements)
2
24
0
2
Order By: Relevance
“…One study evaluated the effect of topical medication on the sleep of patients with DED and suggested that a consultation-liaison psychiatry service (i.e., collaboration with psychiatrists and other medical specialists may be helpful for patients with DED and potential psychiatric problems). 102 The study evaluated sleep quality in 71 patients with DED using a questionnairebased survey before and after topical treatment for DED. The effectiveness of sleep and ophthalmic services in assisting with sleep problems in patients with eye disease was assessed using the PSQI and HADS.…”
Section: Ophthalmic Measures Followed By a Consultation-liaison Psychmentioning
confidence: 99%
“…One study evaluated the effect of topical medication on the sleep of patients with DED and suggested that a consultation-liaison psychiatry service (i.e., collaboration with psychiatrists and other medical specialists may be helpful for patients with DED and potential psychiatric problems). 102 The study evaluated sleep quality in 71 patients with DED using a questionnairebased survey before and after topical treatment for DED. The effectiveness of sleep and ophthalmic services in assisting with sleep problems in patients with eye disease was assessed using the PSQI and HADS.…”
Section: Ophthalmic Measures Followed By a Consultation-liaison Psychmentioning
confidence: 99%
“…Symptoms rarely completely disappear, while their reduction positively affects patients' quality of life and improves sleep and mood disorders 4 5…”
Section: Introductionmentioning
confidence: 99%
“…Ayaki et al40 revealed that topical treatment with eye drops significantly improved PSQI in patients with DED, and the improvement was greater in newly diagnosed DED compared to established DED, suggesting that DED may also influence sleep disorder and that early treatment of DED can also improve sleep quality. They also reported that combination of sleep services and topical treatment with eye drops could successfully treat patients with sleep disorders overlapped with DED 40…”
Section: Association With Psychiatric Problemsmentioning
confidence: 99%
“…Treatment of accompanying psychiatric or neurological problems can be helpful in alleviating dry eye symptoms. Considering the reciprocal influence between DED and psychiatric disorders, comprehensive management of both conditions would be more beneficial 40,81…”
Section: Managementmentioning
confidence: 99%